How a token-based game may elicit the reward prediction error and increase engagement of students in elementary school. A pilot study - Eckert, Marcus; Scherenberg, Viviane; Klinke, Clemens (Frontiers in Psychology, 2023)
Student engagement is essential to academic success and student-wellbeing. In the past, fostering engagement though extrinsic rewards has often been found to be of limited effectiveness over the long term. However, extrinsic rewards are important for improving engagement with non-intrinsically rewarding activities. Thus, in the present study a mechanism that is meant to prolong the effects of extrinsic rewards was investigated: the reward prediction error. This error occurs when rewards are awarded contrary to the awardee’s expectations. In a quasi-experiment, 39 elementary school students participated in a classroom-based game, which was supposed to motivate them to solve math exercises. It combined reinforcement with elements of luck, which were supposed to elicit the reward prediction error. After two weeks, the intervention group had completed significantly more math exercises compared to a pretest (Z = -5.22, p < .001, d = 1.03) and, importantly, also more correctly solved exercises (Z = -4.97, p < .001, d = .85) than a control group. This suggests that game-based reinforcement that elicits the reward prediction error might help to increase student engagement over the medium term. It furthermore highlights the importance of applying gamification elements not only digitally but also in analogue settings.